2010
DOI: 10.1063/1.3504194
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-pressure phase diagram and ferroelectric properties of BaTiO3 single crystal based on a modified Landau potential

Abstract: Misfit strain dependence of ferroelectric and piezoelectric properties of clamped (001) epitaxial Pb(Zr0.52,Ti0.48)O3 thin films Appl. Phys. Lett. 99, 252904 (2011) Phase transitions in ferroelectric-paraelectric superlattices J. Appl. Phys. 110, 114109 (2011) Dielectric and nonlinear current-voltage characteristics of rare-earth doped CaCu3Ti4O12 ceramics J. Appl. Phys. 110, 094101 (2011) Scanning electro-optic microscopy of ferroelectric domain structure with a near-field fiber probe J. Appl. Phys. 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 44 publications
3
61
0
Order By: Relevance
“…Previous works have employed a similar technique to determine the electric field-27, 44 and hydrostatic stress-dependent 48 evolution of polarization in perovskite ferroelectrics. Haun et al 49 have provided approximations of the Landau coefficients up to the 6 th order for numerous PZT compositions.…”
Section: G(p;σmentioning
confidence: 99%
“…Previous works have employed a similar technique to determine the electric field-27, 44 and hydrostatic stress-dependent 48 evolution of polarization in perovskite ferroelectrics. Haun et al 49 have provided approximations of the Landau coefficients up to the 6 th order for numerous PZT compositions.…”
Section: G(p;σmentioning
confidence: 99%
“…The intensity of tetragonal peaks decreases significantly after HPT processing at large strains (N = 1-5 or γ = 27-137), indicating that a decrease in tetragonality and a transition to the cubic phase could have occurred, consistent with the BTO phase diagram. [16][17][18] Details concerning the BTO Raman spectra were reported elsewhere. [21][22][23][24] These results clearly show that, although substantial pressure is required to trigger the cubic-phase formation, the phase transition is facilitated with straining.…”
mentioning
confidence: 99%
“…[9] Moreover, BTO has been widely investigated for its optical properties, [10] photoluminescence (PL), [11,12] photocatalysis, [13] proton conductivity [14] and phase transformations. [15][16][17][18][19][20][21][22][23][24] BTO transforms from a rhombohedral structure to an orthorhombic phase at − 90°C, to a ferroelectric tetragonal phase at 5°C, and to a paraelectric cubic phase at 120°C under ambient pressure. [15][16][17][18] At ambient temperature, it exhibits a tetragonal-to-cubic phase transformation at 2 GPa [15][16][17][18] and it disorders at 5 GPa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Landau polynomial as originally applied to ferroelectric barium titanate by Devonshire 188,189 has been elaborated on many times, and several alternative expressions for the free energy have been reported that reproduce experimental data with varying degrees of agreement. [190][191][192][193][194] The situation for ferroelectric solid solutions is more complicated still, because the dependence of the theory parameters on composition must also be explicitly determined. 195,196 Approaches for doing so that utilize analytical parameterization schemes have recently been reported.…”
Section: Challenges For Modeling Of Complex Oxide Heterostructuresmentioning
confidence: 99%